NITROGEN PROCESSING IN THE HYPORHEIC ZONE OF A PASTORAL STREAM - Storey R.G.; Williams D.D.; Fulthorpe R.R. (My University, 2004)
The distribution of nitrogen-transforming processes, and factors controlling their rates, were determined within the hyporheic zone of a lowland stream draining agricultural land. In the field, physicochemical parameters were measured along a 10 m-long hyporheic flow line between downwelling and upwelling zones. Sediment cores were retrieved from the stream bed surface, and from 20, 40 and 60 cm deep in each zone, and in the laboratory, water from the corresponding depth was percolated through each core at the natural flow rate. Concentrations of nitrogen species and oxygen were measured before and after flow through each core. Denitrification was measured using a 15N-nitrate tracer. Shallow and downwelling zone samples were clearly distinct from deeper and upwelling zone samples in terms of physicochemical conditions, microbial processes and factors controlling nitrogen processing. Denitrification was highest in surface and downwelling zone cores, despite high oxygen levels, probably due to high pore-water nitrate concentrations in these cores and isolation of the denitrifying bacteria from oxygen in the bulk water by the hyporheic biofilms. Denitrification was limited by oxygen inhibition in the downwelling group, and by nitrate availability in the upwelling group. Strong evidence indicated that dissimilatory nitrate reduction to ammonium, occurred in almost all cores, and outcompeted denitrification for nitrate. In contrast, nitrification was undetectable in all but two cores, probably because of intense competition for oxygen. Field patterns and lab experiments indicated that the hyporheic zone at this moderately N-rich site is a strong sink for nitrate, fitting current theories that predict where hyporheic zones are nitrate sinks or nitrate sources.
Keywords: DENITRIFICATION; DNRA; HYPORHEIC ZONE; NITRIFICATION; NUTRIENT DYNAMICS; STREAM ECOLOGY